Combined SPECT Imaging of Regional Cerebral Blood Flow (99mTc-HexamethylPropyleneamine Oxime, HMPAO) and Blood Volume (99mTc-RBC) to Assess Regional Cerebral Perfusion Reserve in Patients with Cerebrovascular Disease - Buell, U.; Braun, H.; Ferbert, A.; Stirner, H.; Weiller, C.; Ringelstein, E. B. (Nuklearmedizin - NuclearMedicine, 1988)
In 53 patients with cerebrovascular disease (CVD), regional cerebral blood flow (CBF) and blood volume (CBV) were imaged by SPECT within one session. Slice division (CBF: CBV) yielded distribution of regional cerebral perfusion reserve (CPR). Semiquantitative evaluation was obtained from manually set ROIs by interhemispherical ratios (for CBF, CBV and CPR), using 2 SD from a normal group (n = 10) as a threshold. Sensitivities were 59% for CBF, 94% for CBV and 83% for CPR. Combined sensitivity was 98%. Establishing three constellations for CBF, CBV and CPR, regionally normal CBFs but quantitatively increased CBVs (+69%) and decreased CPRs (−31 %) were found in relatively early stages of CVD. Very advanced cases showed decreased CBFs (−65%), CBVs (−40%), CPRs (−49%) and a surrounding penumbra. In 87% (46/53 patients), such Theologically postulated constellations could be demonstrated. We conclude that combined CBF and CBV SPECT, assisted by CPR images, is a promising tool to detect CVD and to assess its individual regional severity.